The Role of Calling on Work Engagement Through Job Crafting Mediation among Guidance and Counseling Teachers - Holisane Angela Keliat; Rahmi Lubis; Ummu Khuzaimah (Journal of Educational, Health and Community Psychology, 2026)
Guidance and counseling teachers play a vital role in supporting students’ academic, social, emotional, and career development, yet their work engagement remains a critical concern. This study aims to examine the effect of calling on work engagement through the mediating role of job crafting among guidance and counseling teachers. A quantitative explanatory design was employed, involving 256 teachers selected using total sampling in Deli Serdang Regency. Data were collected using the Utrecht Work Engagement Scale (UWES-9), Calling and Vocation Questionnaire (CVQ), and Job Crafting Scale (JCS), and analyzed using Structural Equation Modeling– Partial Least Squares (SEM-PLS). The results reveal that calling has a positive and significant effect on both work engagement and job crafting, while job crafting also positively influences work engagement. Furthermore, job crafting significantly mediates the relationship between calling and work engagement. These findings emphasize the importance of enhancing calling and proactive job crafting behaviors to improve teachers’ work engagement.